The combined acute effects of massage, rest periods, and body part elevation on resistance exercise performance - Caruso, J. F.; Coday, M. A. (The Journal of Strength and Conditioning Research, 2008)
Although massage administered between workouts has been suggested to improve recovery and subsequent performance, its application between bouts of repetitive supramaximal anaerobic efforts within a given workout has received little attention. The purpose of the study compared different forms of very short rest periods administered between resistance exercise sets of individual workouts on subsequent performance. With a within-subjects design methodology, subjects (n = 30) performed three workouts that were identical in terms of the exercises (45° leg press, prone leg curl, seated shoulder press, standing barbell curl), number of sets, and the resistance employed. For each workout, subjects received one of the following treatments between sets: 1 minute of rest as they stood upright, 30 seconds of rest as they stood upright, or 30 seconds of concurrent massage and body part elevation (MBPE), which entailed petrassage of the exercised limbs in a raised and supported position in an attempt to abate fatigue and enhance recovery from the previous set. Subjects were instructed to perform as many repetitions as possible for each set. For each exercise, two dependent variables were calculated: a total work/elapsed time ratio and the cumulative number of repetitions performed. For each exercise, one-way repeated-measures analysis of variance and Tukey's post hoc test revealed the following total work/elapsed time results: 1 minute rest <30 seconds' rest, 30 seconds' MBPE. For each exercise, cumulative repetition results were as follows: 1 minute rest >30 seconds' rest, 30 seconds' MBPE. Results imply that rest period duration exerts more influence on resistance exercise performance than MBPE. Those who seek improved resistance exercise performance should pay particular attention to rest period durations.